The effect of psychological empowerment on withdrawal behaviours as mediated by organisational citizenship behaviour and work engagement in a South African military university - Semenya, Linda Dineo (Stellenbosch : Stellenbosch University, 2021)
Thesis (MCom)--Stellenbosch University, 2021.